The effects of proline, carnitine on the viability of sperm stored at 5oC (chilled semen) - Polmer Situmorang; E Triwulanningsih; A Lubis; W Caroline; T Sugiarti (Indonesian Center for Animal Research and Development (ICARD), 2001)
An experiment was carried out to evaluate the addition of proline, carnitine in Tris-extender on the viability of bull sperm following storage at 5oC. Semen was collected by means of artificial vagina (AV), diluted in Tris-extender containing 5% V/V egg yolk (EY) and 4% V/V glycerol to get a final concentration of 50 million sperms/ml. Diluted semen cooled to 5oC for 45 minute and stored at those temperature for 1, 3, 10, and 13 days. In the first activity the addition of 15, 30 and 60 mM carnitine in Tris-extender while in the second activity the inclusion of 15, 30, and 60 mM proline on the viability of sperm was investigated. Addition of carnitine to Tris-extender signifinatly increase (P<0.05) the viability of sperm after storage for more than 3 days. At 3 days of storage, the mean %M and %L were 27.3, 38.8, 33.5, 53.0, 31.8, 47.0, and 30.5, 46.8 for control 15, 30, and 60 mM carnitine respectively. The similar results was obtained for 7 days of storage where the mean %M and %L for control (12.5 and 27.3) was significantly lower (P<0.05) than those 15, 30, and 60 mM carnitine (15.0, 33.5, 18.8, 36.5, 17.5, 36.3). The superiority of carnitine was maintained for 10 days of storage, where the mean %L were 23.5, 28.8, 31.5, and 30.3 for control; 15; 30; and 60 mM respectively. There was no any significant within concentration of carnitine tested (15 to 60 mM).The condition of apical ridge was not significantly affected by carnitine. In the second activity, inclusion of proline to Trisextender statistically (P<0.05) improved the viability of sperm after storage for 7 and 13 days. After 7 days of storage the mean %M and %L were 31.4, 36.4, 38.8, 40.4, 36.6, 42.7, and 34.8, 43.3 for control; 15, 30, and 60 mM proline respectively. The significant effects of proline was remain for 13 days of storage where the mean %M and % L were 24.6, 32.9, 28.6, 37.5, 29.1, 39.8, and 30.1, 37.3 for control; 15, 30, and 60 mM proline respectively. There was no significant difference within the concentration of proline. Condition of apical ridge was not significantly affected by proline. Key words: Sperm, viability, carnitine, proline